2021
DOI: 10.3390/ijms22063055
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII-A: An Indispensable “Factor” in Haemostasis and Wound Healing

Abstract: Factor XIII (FXIII) is a transglutaminase enzyme that catalyses the formation of ε-(γ-glutamyl)lysyl isopeptide bonds into protein substrates. The plasma form, FXIIIA2B2, has an established function in haemostasis, with fibrin being its principal substrate. A deficiency in FXIII manifests as a severe bleeding diathesis emphasising its crucial role in this pathway. The FXIII-A gene (F13A1) is expressed in cells of bone marrow and mesenchymal lineage. The cellular form, a homodimer of the A subunits denoted FXII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 217 publications
(273 reference statements)
0
47
0
Order By: Relevance
“…This localizes important amounts of active FXIII-A directly at sites of thrombus formation. 4 Indeed, Mitchell et al 5 demonstrated that platelet FXIII-A exerts an antifibrinolytic function by cross-linking α2-antiplasmin into the fibrin network adjacent to platelet aggregates. Subsequently, Mattheij et al 20 showed that on the surface of the platelet subpopulation expressing negatively charged procoagulant phospholipids upon activation by collagen and thrombin, fibrinogen bound to activated αIIbβ3 and cross-linked by cFXIIIa is responsible for the formation of so-called "star-like fibrin fiber formation", 21 thought to be involved in the anchorage of these platelets within the thrombus and eventually stabilization of the platelet-fibrin clot.…”
mentioning
confidence: 99%
“…This localizes important amounts of active FXIII-A directly at sites of thrombus formation. 4 Indeed, Mitchell et al 5 demonstrated that platelet FXIII-A exerts an antifibrinolytic function by cross-linking α2-antiplasmin into the fibrin network adjacent to platelet aggregates. Subsequently, Mattheij et al 20 showed that on the surface of the platelet subpopulation expressing negatively charged procoagulant phospholipids upon activation by collagen and thrombin, fibrinogen bound to activated αIIbβ3 and cross-linked by cFXIIIa is responsible for the formation of so-called "star-like fibrin fiber formation", 21 thought to be involved in the anchorage of these platelets within the thrombus and eventually stabilization of the platelet-fibrin clot.…”
mentioning
confidence: 99%
“…Coagulation factor XIII (FXIII), a transglutaminase that stabilizes the fibrin mesh against mechanical stress and proteolysis, is present at high concentrations in platelet cytosol [ 63 ]. During convulxin/thrombin activation, platelet FXIII is externalized by a receptor-signaling dependent mechanism on the membrane of procoagulant COAT platelets [ 64 ], where it appears to serve several functions, such as cross-linking α2-antiplasmin into fibrin [ 65 ], promoting star-like fibrin fiber formation [ 62 ], and retaining α-granule proteins [ 36 ].…”
Section: Procoagulant Platelet Characterizationmentioning
confidence: 99%
“…Plasma factor XIII, a 325.8 kDa heterotetrameric proenzyme which stabilizes fibrin, is composed of two catalytic A subunits (FXIII-A) and two inhibitory B subunits (FXIII-B) (Ashcroft et al, 2000;Muszbek et al, 2011;Singh et al, 2019). It is the last factor in the coagulation cascade and facilitates crosslinking between fibrin monomers, protects fibrin from shear stress, and guards clots from premature degradation (Duval et al, 2014;Vasilyeva et al, 2018;Alshehri et al, 2021). For factor XIII to react with fibrin monomers, it is converted to an activated transglutaminase and functions in the presence of thrombin and Ca 2+ .…”
Section: Ca 2+ Binding To Factor XIII Regulates the Crosslinking Of Fibrin Monomersmentioning
confidence: 99%